Preparation, characterization, and. drug-release properties of poly(N-isopropylacrylamide) Microspheres having poly(itaconic acid) graft chains - KAYAMAN APOHAN, NİLHAN (WILEY, 2005)
An inverse suspension polymerization method for the preparation of thermoresponsive hydrogel microspheres based on N-isopropylacrylamide was described in this article. The polymerization reaction was carried out at 200 rpm stirring rate and the microspheres obtained were in the size range of 71-500 mu m in the swollen states. The particles were sieved by using ASTM sieves. The selected fraction (180-250 mu m) of poly(N-isopropylacrylamide) (PNIPAAm) microspheres was used for radiation-induced modification with itaconic acid (TA) to obtain PNIPAAm/poly(itaconic acid) graft copolymer. Viagra and lidocaine were used as model drugs for the investigation of controlled-release behavior of the microspheres. Incorporation of IA graft chains onto microspheres enhanced significantly the uptake of both drugs and further controlled release at specific pH values. The release studies showed that some of the basic parameters affecting the drug-loading and -release behavior of the microspheres were pH, temperature, particle size, and chemical nature of drug. (c) 2005 Wiley Periodicals, Inc.
Keywords: microspheres; N-isopropylacrylamide; itaconic acid; drug release; COPOLYMERIC HYDROGELS; PHASE-TRANSITION; BEADS; TEMPERATURE; ADSORPTION; WATER